Performance Analysis of Self-Consumed Solar PV System for A Fully DC Residential House - T. M. N. T. Mansur; N. H. Baharudin; R. Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Malaysia is moving forward by promoting used of renewable energy such as solar PV to the public where it is generated at the distribution voltage level. The fluctuation of fuel prices becomes main concern to the consumers since it affecting the electricity tariff. The objective of this project is to design a self-consumed DC power system for a residential house from renewable energy resource which is solar PV that it will independent from the utility grid. The methodology proposed are configuring daily load demand, sizing PV array and battery bank and simulation of the design system by using PVsyst. Based on solar energy resource, the optimum PV array size is 2.0 kWp while the battery bank size is 700 Ah at 48 V which is designated for 4 days of autonomy. The system could meet 100% of load demand throughout the year with 67.9% of performance ratio. The loss to the system is contributed by the temperature effect to the PV module, unused energy because of battery full capacity, converter and battery efficiencies. Using this concept, the proposed design set-up is expected to benefit the residential consumers in reducing utility electricity consumption up to 2,434 kWh per year and avoiding 1.7 tons of carbon emissions into the environment annually.